VD_FINDINFO AVS 59/12 ap. TF - 42/2014 vom 23. Oktober 2014 - VD Tribunal cantonal (2014)
SALAIRE DÉTERMINANT, FRAIS GÉNÉRAUX, REPRISE, COTISATION AVS/AI/APG, MOYEN DE PREUVE | 5 al. 2 LAVS, 9 al. 1 RAVS, 9 al. 2 RAVS